Exploring the link between economic policy uncertainty, financial development, ecological innovation and environmental degradation; evidence from OECD countries. - Xiaowei Zheng; Muhammad Faheem; Khusniddin Fakhriddinovch Uktamov (PLoS ONE)
Governments have been concerned with balancing economic growth and environmental sustainability. Nevertheless, it has been noted that sustainable development is interconnected with economic variables, the institutional framework, and the efficacy of ecological regulatory measures. This study experimentally examines the correlation of economic policy uncertainty (EPU), financial development (FD), ecological innovation (EI), corruption (IQ), foreign direct investment (FDI), trade openness (TR), natural resource rent (NRR), and CO2 emission. We utilized longitudinal data from the Organization for Economic Cooperation and Development (OECD) countries from 2003 to 2021 to address the existing research void. This study used sequential processes of the linear panel data model (SELPDM) and the SYS-GMM approaches in obtaining consistent and efficient results. The inverse U-shaped relationship between FD and environmental degradation (ED) is confirmed by the long-term elasticity estimates generated by the SELPDM method Elasticity estimates for the long-run show that rigorous ecological regulations, higher renewable energy utilization, higher FD and less corruption, an interaction between FD and rigorous ecological regulations all contribute to reduced ED. Its also being observed that both EPU, FDI and trade openness are positively affecting the ED. It confirms the idea of pollution refuge between the OECD countries. The causality test results show that corruption and FD had reciprocal links with ED, while FDI, trade openness and strict environmental policies were also found to have bidirectional linkage with ED. To achieve sustainable development and prevent environmental degradation in the long term, we propose implementing an institutional financial framework and FD in OECD nations. This may be accomplished by focusing on the effectiveness of environmental regulatory laws and creating a conducive institutional environment.